Management Of Thrips Infesting Mung Bean Using Pesticides - Yasmin, S; Latif, MA; Ali, M; Rahman, MM (SAARC Journal of Agriculture, 2020)
The study was conducted to evaluate the effect of bio-pesticides and chemical insecticides namely Novastar 56EC, Stargate 48SC, Confidor 70WG, Actara 25aWG, Tracer 45SC, Ecomec 1.8EC, Bioneem plus 1EC to control thrips infesting mung bean in the experimental field of Sher-e- Bangla Agricultural University during November 2017 to February 2018. An untreated control observation was also evaluated. Efficacy of the treatments differed significantly and showed effective results in reduction of thrips population and infestation on mung bean at vegetative and reproductive growth stages of the plant. Stargate 48SC (clothianidin) was the most effective insecticide against the thrips species Megalurothrips usitatus and Thrips palmi with the highest reduction of population on top trifoliate leaves and terminal shoots (100.00 and 89.40%, respectively) at vegetative stage and reduction on flower buds and flowers (86.04 and 85.95%, respectively) at reproductive stage of mung bean. The lowest flower bud and flower infestation (7.22 and 3.41%, respectively) and shedding (4.21 and 1.06%, respectively) by thrips with the highest number of pod (23.80 plant-1), seed (10.20 pod-1), 1000 seed weight (48.40 g) and yield (1026.91 kg ha-1) were also found in Stargate 48SC treated plots followed by Confidor 70WG and Actara 25WG treatments. SAARC J. Agri., 17(2): 43-52 (2019)